2016
DOI: 10.1016/j.homp.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic therapy in pediatric atopic diseases: short- and long-term results

Abstract: The results seem to confirm that homeopathic medicine produces positive therapeutic response in atopic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Another study involving adjunctive homeopathic treatment demonstrated that participants felt improved overall health and subjective well‐being using adjunctive homeopathic treatment as a supportive therapy in cancer care 34 . As shown in a longitudinal study within an integrative pediatric practice, homeopathic treatment appeared to reduce the severity of atopic dermatitis and asthma, increased the likelihood of complete resolution, and further demonstrated a reduction in the progression of atopic diseases into adulthood 35 . Researchers showed 75.8% of children with atopic disease had moderate or major improvement in their symptoms with complete remission in 70.1% after 5 to 10 years 35 …”
Section: Review Of the Literature On Homeopathymentioning
confidence: 95%
See 3 more Smart Citations
“…Another study involving adjunctive homeopathic treatment demonstrated that participants felt improved overall health and subjective well‐being using adjunctive homeopathic treatment as a supportive therapy in cancer care 34 . As shown in a longitudinal study within an integrative pediatric practice, homeopathic treatment appeared to reduce the severity of atopic dermatitis and asthma, increased the likelihood of complete resolution, and further demonstrated a reduction in the progression of atopic diseases into adulthood 35 . Researchers showed 75.8% of children with atopic disease had moderate or major improvement in their symptoms with complete remission in 70.1% after 5 to 10 years 35 …”
Section: Review Of the Literature On Homeopathymentioning
confidence: 95%
“…34 As shown in a longitudinal study within an integrative pediatric practice, homeopathic treatment appeared to reduce the severity of atopic dermatitis and asthma, increased the likelihood of complete resolution, and further demonstrated a reduction in the progression of atopic diseases into adulthood. 35 Researchers showed 75.8% of children with atopic disease had moderate or major improvement in their symptoms with complete remission in 70.1% after 5 to 10 years. 35 of Similars, which states that a substance capable of creating symptoms in one who is healthy can be used to treat those same symptoms in one who is sick, popularly known as like cures like.…”
Section: Conditions Treated Using Homeopathymentioning
confidence: 99%
See 2 more Smart Citations